Diminished medial prefrontal cortex activation during the recollection of stressful events is an acquired characteristic of PTSD. Issue 7 (12th September 2017) - Dahlgren, M. K.; Laifer, L. M.; VanElzakker, M. B.; Offringa, R.; Hughes, K. C.; Staples-Bradley, L. K.; Dubois, S. J.; Lasko, N. B.; Hinojosa, C. A.; Orr, S. P.; Pitman, R. K.; Shin, L. M.
Abstract: Background: Previous research has shown relatively diminished medial prefrontal cortex activation and heightened psychophysiological responses during the recollection of personal events in post-traumatic stress disorder (PTSD), but the origin of these abnormalities is unknown. Twin studies provide the opportunity to determine whether such abnormalities reflect familial vulnerabilities, result from trauma exposure, or are acquired characteristics of PTSD. Methods: In this case–control twin study, 26 male identical twin pairs (12 PTSD; 14 non-PTSD) discordant for PTSD and combat exposure recalled and imagined trauma-unrelated stressful and neutral life events using a standard script-driven imagery paradigm during functional magnetic resonance imaging and concurrent skin conductance measurement. Results: Diminished activation in the medial prefrontal cortex during Stressful v. Neutral script-driven imagery was observed in the individuals with PTSD, relative to other groups. Conclusions: Diminished medial prefrontal cortex activation during Stressful v. Neutral script-driven imagery may be an acquired characteristic of PTSD. If replicated, this finding could be used prospectively to inform diagnosis and the assessment of treatment response.